Enhanced Control of Single-Stage PV-STATCOM Using Hybrid MPPT and Adaptive AHLMS for Power Quality Improvement - Ibrahim, Nagwa F.; Elzein, I. M.; Mahmoud, Mohamed Metwally; El-Rifaie, Ali M.; Hussein, Hany S.; Elsayed Eid, Mohammed A. (IEEE access, 2025)
This paper introduces an enhanced control strategy for a single-stage PV-STATCOM integrated with a power system. The system is designed to efficiently deliver solar energy to both the load and the grid while significantly improving power quality (PQ). It employs a Hybrid pelican and perturb and observe (HPPO) and Particle Swarm Optimization (PSO) based Maximum Power Point Tracking (MPPT) algorithm to consistently extract peak power from the PV array. AHLMS, with its adaptive hysteresis load management system, generates reference signals for both active and reactive grid currents for controlling the switching operation of a voltage source converter. In addition, this intelligent procedure tunes the control parameters in real-time to reduce tracking errors and adapts dynamically to environmental variations, including solar irradiance, load imbalances, and nonlinearities. The proposed PV-STATCOM is considered PQ-enhanced because it provides reactive power compensation, suppresses harmonic distortion (HD), stabilizes system voltages, and improves the power factor (PF). The output current remains sinusoidal and fits well with minimal HD while complying with IEEE-519 standards. Mathematical simulation in MATLAB/Simulink were applied, along with comparisons to the most recent methodologies, ensures that this system outperforms others under varying sunlight, nonlinear, and unbalanced loading conditions.